Analysis of Mental Health and Quality of Life of Mount Lawu : The Perspective of Elderly Climbers - Sri Maryani; Mustika Fitri; Mohammad Zaky; Hilmy Apriady (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study analyzes the mental health and quality of life of Mount Lawu climbers from the perspective of elderly climbers. Using quantitative descriptive methods, we included 17 participants who filled out the Center for Epidemiologic Studies Depression Scale (CES-D) questionnaire to measure mental health and the Older People's Quality of Life (OPQOL-35) questionnaire to measure quality of life. The results showed that the average OPQOL score was 38.66 with a standard deviation of 4.52, while the average CESDR score was 21.60 with a standard deviation of 2.22. These findings showed that there was variation in quality of life and depression levels among participants, with quality of life more varied than depression levels. These results underscore the importance of interventions that support physical and mental health to improve the well-being of the elderly. A more detailed study is needed to know more about the factors that affect mental health and quality of life in this population.